Effects of AT1 receptor antagonism on interstitial and ultrastructural remodeling of heart in response to a hypercaloric diet - Oliveira-Junior, Silvio A.; Dal Pai, Maeli [UNESP]; Guizoni, Daniele M. [UNESP]; Torres, Barbara P. [UNESP]; Martinez, Paula F.; Campos, Dijon H. S. [UNESP]; Okoshi, Marina P. [UNESP]; Okoshi, Katashi [UNESP]; Padovani, Carlos R. [UNESP]; Cicogna, Antonio C. [UNESP] (Wiley, 2019)
Palatable hypercaloric feeding has been associated with angiotensin-II type 1 receptor (AT1R) stimulation and cardiac remodeling. This study analyzed whether AT1R antagonism attenuates cardiac remodeling in rats subjected to a palatable hypercaloric diet. Male Wistar-Kyoto rats were subjected to a commercial standard rat chow (CD) or a palatable hypercaloric diet (HD) for 35 weeks and then allocated into four groups: CD, CL, HD, and HL; L groups received losartan in drinking water (30 mg/kg/day) for 5 weeks. Body weight, adiposity, and glycemia were evaluated. The cardiovascular study included echocardiography, and myocardial morphometric and ultrastructural evaluation. Myocardial collagen isoforms Type I and III were analyzed by Western blot. Both HD and HL had higher adiposity than their respective controls. Cardiomyocyte cross-sectional-area (CD 285 ± 49; HD 344 ± 91; CL 327 ± 49; HL 303 ± 49 μm 2 ) and interstitial collagen fractional area were significantly higher in HD than CD and unchanged by losartan. HD showed marked ultrastructural alterations such as myofilament loss, and severe mitochondrial swelling. CL presented higher Type I collagen expression when compared to CD and HL groups. The ultrastructural changes and type I collagen expression were attenuated by losartan in HL. Losartan attenuates systolic dysfunction and ultrastructural abnormalities without changing myocardial interstitial remodeling in rats subjected to a palatable hypercaloric diet.
Keywords: Angiotensin; Arterial Pressure; Cardiac Remodeling; Collagen; High-Fat Diet; Ultrastructure